Use of Information Communication Technology in communicable disease surveillance - Chandrasekar, K. (Sri Lanka Journal of Bio-Medical Informatics, 2011)
Panic set out by newly emerging and re-emerging communicable diseases is taking a global dimension. A functional surveillance system is essential in all countries to provide the necessary information required for preventive action against communicable diseases and to make decisions on public health related issues. This article discusses the importance of such communicable disease surveillance systems (CDSS) and problems with existing CDSS. Most of the studies conducted were related to the attributes such as accuracy and speed of communicable disease notification. As a solution to overcome the difficulties experienced by the existing systems, some countries have introduced computerised systems for the surveillance of communicable diseases. Studies focused on the evaluation of these electronic systems reported improvements in the quality of the systems with respect to the previous systems. During the last few years, studies were directed towards the development and evaluation of „early warning systems‟ and „syndromic surveillance systems‟ for early detection and monitoring of epidemics and bioterrorism-initiated infectious disease outbreaks. The WHO envisages an integrated approach to communicable disease surveillance and this strategy has been recognised by all member states and is being adopted in the African region and activities are under way in the Eastern Mediterranean region, Europe and South-East Asia.
Keywords: communicable disease surveillance; disease notification